2012
DOI: 10.1158/0008-5472.can-12-0614
|View full text |Cite
|
Sign up to set email alerts
|

OTX2 Represses Myogenic and Neuronal Differentiation in Medulloblastoma Cells

Abstract: The brain development transcription factor OTX2 is overexpressed and/or genomically amplified in most medulloblastomas, but the mechanistic basis for its contributions in this setting are not understood. In this study we identified OTX2 as a transcriptional repressor and a gatekeeper of myogenic and neuronal differentiation in medulloblastoma cells. OTX2 binds to the MyoD1 core enhancer through its homeobox domain and the remarkable repressor activity exhibited by the homeobox domain renders OTX2 transcription… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 49 publications
0
28
1
Order By: Relevance
“…The suppressor activity of Otx2 has been previously documented in the cerebellum and the retina, and during myogenesis and neurogenesis (Bai et al, 2012;Nishida et al, 2003;Puelles et al, 2006Puelles et al, , 2003. Sox2 and Otx2 are able to interact directly via their HMG and homeobox DNA-binding domains, respectively (Danno et al, 2008), and Otx2 has been shown to suppress the expression of Sox2 during retinal differentiation (Nishihara et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The suppressor activity of Otx2 has been previously documented in the cerebellum and the retina, and during myogenesis and neurogenesis (Bai et al, 2012;Nishida et al, 2003;Puelles et al, 2006Puelles et al, , 2003. Sox2 and Otx2 are able to interact directly via their HMG and homeobox DNA-binding domains, respectively (Danno et al, 2008), and Otx2 has been shown to suppress the expression of Sox2 during retinal differentiation (Nishihara et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse glioma cell line GL261 cells were kindly provided by Dr. Michael Lim's laboratory at the Johns Hopkins University in 2009 and human medulloblastoma cell line D425Med (D425) was obtained from the Duke University Brain Tumor Center without further authentication (3, 15). GL261 and D425 cells were maintained in DMEM media supplemented with 10% fetal bovine serum and antibiotics at 37°C in humidified air containing 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…We focused on dmbx1, which we hypothesize functions to promote cell cycle exit (Wong et al, 2010) and its putative interaction with vsx2. Vertebrate Dmbx1 is thought to function as a transcriptional repressor (Bai et al, 2012;Berry et al, 2006;Kimura et al, 2005;Yao and Kessler, 2001), but its targets are largely unknown. The vertebrate Vsx2 gene is required for embryonic cells to maintain a proliferative RPC identity (Burmeister et al, 1996;Horsford et al, 2005), in part through its function in repressing genes that would otherwise specify different retinal cell fates Vitorino et al, 2009).…”
Section: Introductionmentioning
confidence: 99%